On the Determinants of Corporate Social Responsibility: International Evidence on the Financial Industry - Chih, Hsiang-Lin (Journal of business ethics, 2010)
This article sets out to undertake a thorough, point-by-point examination of the theory postulated by Campbell (2007), in which an attempt is made to specify the conditions under which corporations may or may not act in socially responsible ways. In order to ensure the overall reliability of our study, and to attempt to provide a new understanding of, and greater insights into, whether corporate social responsibility (CSR) is affected by financial and institutional variables, we empirically investigate a total of 520 financial firms in 34 countries, between the years 2003 and 2005. Our empirical findings are: (i) firms with larger size are more CSR minded, and the financial performance and CSR are not related; (ii) firms would actually act in more socially responsible ways to enhance their competitive advantages when the market competitiveness is more intense; (iii) financial firms in countries with stronger levels of legal enforcement tend to engage in more CSR activities; however, interestingly and rather strikingly, those firms in countries with stronger shareholder rights tend to engage in less CSR activities; and (iv) self-regulation within the financial industry has a significantly positive effect on CSR, with firms being found to act in more socially responsible ways in those countries which have more cooperative employer–employee relations, higher quality management schools, and a better macroeconomic environment.